PENGARUH LITERASI KEUANGAN, PENGETAHUAN KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN PADA PELAKU USAHA UMKM Di CIKARANG - Muhammad Rifki; Jelfi Putra Jaya Lase; Denison Zebua; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study aims to examine the influence of financial literacy, financial knowledge, and financial attitudes on the financial management behavior of culinary MSME actors in South Cikarang. Data collection was carried out by a quantitative survey method through an online questionnaire distributed to 50 MSME actors who met the purposive sample criteria. Data analysis uses validity, reliability, and multiple linear regression tests. The results of the study show that there are three aspects that affect financial management behavior, namely financial literacy, financial knowledge, and financial attitudes. Financial literacy has a non-significant influence, while financial literacy and financial attitudes exert a partially significant influence. The results of this study recommend the creation of a more effective financial literacy program for MSME actors to improve the performance and sustainability of their businesses.